Determinan Modal Manusia Dan Akses Internet Terhadap Kemiskinan Di Indonesia - Rahmawati, Lusy; Yeni, Isra (Universitas Negeri Padang, 2025)
Poverty is a problem that affects almost every country, including Indonesia as a developing nation. Poverty is multidimensional, with its causes not limited to a single factor but can occur due to several factors. This study aims to determine and analyze the effect of education, health and internet access on poverty in Indonesia in 2019-2023. This study uses a panel data regression equation analysis model in Eviews12 with the Fixed Effect Model (FEM) approach. The results of this study indicate that (1) education has a positive and significant effect on poverty, (2) health has a negative and significant effect on poverty, (3) internet access has a positive and significant effect on poverty, (4) provincial minimum wage has a negative and significant effect on poverty in Indonesia, (5) local revenue has a negative and not significant effect on poverty in Indonesia.